Expression of LEP, LEPR and PGC1A genes is altered in peripheral blood mononuclear cells of patients with relapsing-remitting multiple sclerosis - Kolić, Ivana; Stojković, Ljiljana; Dinčić, Evica; Jovanović, Ivan; Stanković, Aleksandra; Živković, Maja (Journal of neuroimmunology, 2020)
Leptin (LEP) may contribute to the pathogenesis of multiple sclerosis (MS) by its immunomodulatory, proinflammatory and prooxidant effects. Therefore, plasma LEP levels and mRNA expression of five genes related to the LEP signaling pathway (LEP, LEP receptor (LEPR), peroxisome proliferator-activated receptor-gamma coactivator 1-alpha (PGC1A), superoxide dismutase 2, tumor necrosis factor-alpha) were investigated in relapsing-remitting MS. In patients (N = 64), compared to healthy subjects (N = 62), relative LEP mRNA levels were significantly increased (p = 0,01), while LEPR and PGC1A mRNA levels were decreased (p = 0,001 and p = 0,04, respectively). Significant positive correlation was observed between LEPR mRNA levels and clinical parameters of MS progression (EDSS, MSSS). [Display omitted] •Significantly higher pLEP is observed in female than in male RRMS patients.•PBMC LEP mRNA is significantly increased in patients, compared to controls.•PBMC LEPR and PGC1A mRNAs are significantly lower in patients than in controls.•Positive correlation is observed between LEPR mRNA levels and both EDSS and MSSS.